2006
DOI: 10.1111/j.1365-2648.2006.03876.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical hand scrubs in relation to microbial counts: systematic literature review

Abstract: Surgical hand scrubs using an alcohol-based product were more effective than a 6-minute scrub using 4% chlorhexidine gluconate. There is no evidence to support a 2-minute surgical hand scrub as being more effective than a 3-minute one using 4% chlorhexidine gluconate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…The average duration of surgeries for doctors using the dry-fast scrubbing solution was 2.5 h, whereas the average duration of surgeries for doctors using the traditional povidone-iodine scrubbing solution was 1.9 h. Regarding their sustained antimicrobial effects, the dryfast scrubbing was more effective compared to the traditional water-based scrubbing. This finding was similar to that reported by Hsieh et al (2006), Lai et al (2012) and Tanner et al (2008). Therefore, the effectiveness of intervention with dry-fast scrubbing is supported with evidence.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The average duration of surgeries for doctors using the dry-fast scrubbing solution was 2.5 h, whereas the average duration of surgeries for doctors using the traditional povidone-iodine scrubbing solution was 1.9 h. Regarding their sustained antimicrobial effects, the dryfast scrubbing was more effective compared to the traditional water-based scrubbing. This finding was similar to that reported by Hsieh et al (2006), Lai et al (2012) and Tanner et al (2008). Therefore, the effectiveness of intervention with dry-fast scrubbing is supported with evidence.…”
Section: Discussionsupporting
confidence: 91%
“…A systematic literature review reported that among dryfast antimicrobial agents, the effects of alcohol scrubbing solutions were superior to chlorhexidine solutions (Hsieh et al, 2006). However, the three studies reviewed in the comparison had different scrubbing duration length and did not uniformly use brushes.…”
Section: Antibacterial Scrubbing Solutions and Antibacterial Effectsmentioning
confidence: 99%
“…Despite innumerous internati onal studies (3,(8)(9)(10)(11)(12)(13)(14) contraindicati ng the use of arti facts for performing hand anti sepsis, the studies found evaluated the effi ciency of mechanical and chemical methods to perform hand antisepsis with the soluti on of chlorhexidine gluconate at 4% instead of 2% (4,9,(15)(16)(17) .…”
Section: Descriptoresmentioning
confidence: 99%
“…It is has been accepted for decades that everyone involved in direct contact with the surgical field or sterile items should perform a surgical scrub and don sterile gloves. Surgical scrub techniques have been evaluated extensively elsewhere (38,39). Recently, application of alcohol-chlorhexidine combinations have been evaluated as a replacement for surgical scrubbing and have been shown to be more effective than standard surgical scrub methods (40,41).…”
Section: Infection Prevention and Controlmentioning
confidence: 99%